Managing capital flows in transition economies with a case-study of Central and Eastern Europe - Zdenek Drabek; Stephany Griffith-Jones (World Trade Organization (WTO), 1998)
Management of capital inflows has unexpectedly become a major challenge in transition economies. These countries were expected to have an insatiable demand for foreign capital, and an excess demand for capital inflows was, therefore, predicted by most observers. Foreign investors are also known to be very selective in their choice of markets, and these countries were a big unknown. Moreover, macroeconomic policy in these countries has been dominated by the objective of disinflation. We explain in this paper the reasons why some transition countries have been an attractive market for foreign investors and how important has foreign capital been for these countries. But the bulk of the paper provides an assessment of government policies to manage foreign capital inflows. We evaluate the policies against the background of different government objectives and in terms of the actual policy instruments used by the monetary authorities, the timing and sequencing and the costs of these interventions. We argue that the initial responses to capital surges were poor; the authorities were reluctant to adjust their original policies and learn from the experiences elsewhere. Eventually, their policy responses were changed but until the costs of inertia became too high. The authorities have effectively used sterilization policies, more flexible exchange rate policies combined with tight monetary and fiscal policies. They also understood that an effective management of capital flows must start from well functioning markets, and have been prepared to adopt structural policies whenever market imperfections could be identified.
Keywords: F32; F41; P27; 330; Capital Flows; Macroeconomic Policy; Transition Economies